Performance Analysis of Field Orientation of Induction Motor Drive Under Open Gate of IGBT Fault - Zakaria Mohamed Salem; Mahmoud Mohamed Elkholy (International Journal of Power Electronics and Drive Systems (IJPEDS), 2013)
This paper  presents a performance analysis of three phase induction motor drive system when fed from three-phase inverter with one IGBT open gate. The drive system is based on indirect rotor field oriented. The performance characteristics of the drive are investigated at healthy operating condition and at faulty condition with IGBT of upper phase leg is opened. The Total Harmonic Distortion of phases current in case opened IGBT are derived. The Simulation of the case study is carried out by using the Matlab/Simulink package on 1.1 kW, 220/380V, 50 Hz three phase induction motor.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.4310